Between actual and virtual reality. Technologies and functionalities of devices in the buying process from the perspective of (Polish) consumers - Guzik, Aldona; Dutka, Grzegorz (Wydawnictwa AGH, 2019)
In modern times, the buying process involves utilisation of technologies from the virtual world as well as appropriate devices and their functionalities. Strategies of this type are also appreciated by young Polish people for whom balancing between actual and virtual reality is becoming an intrinsic element of consumer awareness. mBased on selected papers and research reports, including their own and ones not yet published, the authors of the paper present various ways of moving between two realities throughout the whole buying process, from the stage of creating needs to completion of the purchase. In this respect, they draw attention to such issues as the kind of devices and their functionalities used or preferred in this process, the differentiation of actions in the individual buying categories, the involvement of third parties in the buying process, responses to messages, and willingness to disclose personal information. In addition to the empirical character (presentation of the relevant data obtained during the research) of the study, the authors consider the extent of autonomy and rationality of consumer decisions. The paper presents empirical research as it was based on the authors' consumer studies, the full descriptions of which, along with the conclusions, are included in two reports constituting elements of a project implemented by the Social Research Institute at the Institute of Philosophy and Sociology of the Pedagogical University of Krakow (IFiS UP) and the Interia Group, under the name »Studies on the construction of an innovative platform, compliant with the latest global trends and enabling creation of services in the Shopping Assistant model«, funded by the Regional Operating Programme for Mazowieckie Province for 2014–2020 (Priority axis 1: Knowledge Economy, Action 1.2 Research and innovation in enterprises, Sub-measure 1.2.1 R&D projects for enterprises).

Współcześnie w procesie dokonywania zakupów wykorzystywane są technologie ze świata wirtualnego oraz odpowiednie urządzenia i ich funkcjonalności. Strategie tego typu zyskują uznanie również wśród młodych Polaków, dla których balansowanie między rzeczywistością realną i wirtualną staje się nieodłącznym elementem świadomości konsumenckiej. Autorzy artykułu – na podstawie wybranych, w tym także jeszcze niepublikowane, artykuły i raporty badawcze (m.in. własnego autorstwa) – prezentują zróżnicowane sposoby poruszania się pomiędzy dwiema rzeczywistościami w całym procesie zakupowym, od etapu kształtowania się potrzeb, do finalizacji zakupu. Zwracają przy tym uwagę na takie kwestie, jak: rodzaj stosowanych lub preferowanych w tym procesie urządzeń i ich funkcjonalności, zróżnicowanie działań w poszczególnych kategoriach zakupowych, zaangażowanie osób trzecich w proces zakupowy, reakcje na komunikaty, skłonność do udostępniania danych osobowych. Oprócz empirycznego charakteru (prezentacja właściwych danych uzyskanych w toku badań) autorzy podejmują refleksję nad zakresem autonomii i racjonalności konsumenckich decyzji. Artykuł ma charakter empiryczny, został bowiem oparty na zrealizowanych przez autorów tekstu badaniach konsumentów, których pełny opis i wnioski zawarte zostały w dwóch raportach stanowiących elementy projektu realizowanego przez Pracownię Badań Społecznych IFiS UP i Grupę Interia, pt.: »Badania dotyczące budowy innowacyjnej platformy zgodnej z najnowszymi światowymi trendami, umożliwiającej tworzenie usług w modelu Shopping Assistant«, finansowanego z Regionalnego Programu Operacyjnego Województwa Mazowieckiego na lata 2014–2020 (1 Oś Priorytetowa Gospodarka Wiedzy, Działanie 1.2 Badania i innowacje w przedsiębiorstwach, Poddziałanie 1.2.1 Projekty badawczo-rozwojowe przedsiębiorstw).
Między rzeczywistością realną a wirtualną. Technologie i funkcjonalności urządzeń w procesie zakupowym z perspektywy (polskich) konsumentów
Studia Humanistyczne AGH
Keywords: consumers; virtual reality; purchase decision process; konsumenci; wirtualna rzeczywistość; proces podejmowania decyzji zakupowych